1994
DOI: 10.1111/j.1365-263x.1994.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety of parents in an Israeli kibbutz population

Abstract: The purpose of the present study was to compare the levels of dental anxiety in both parents of children in a kibbutz in Israel. Sixty pairs of parents between 22 and 56 years of age with children aged 1-14 years comprised the study population. The parents were divided into three age groups: 22-34 years, 35-44 years, and 45-56 years. Dental anxiety was assessed by using Corah's Dental Anxiety Scale and Kleinknecht's Dental Fear Survey. The mothers showed significantly higher levels of dental anxiety than the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
13
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
5
13
0
3
Order By: Relevance
“…The finding that females reported higher dental anxiety is in accordance with many previous reports (2)(3)(4)(5)(6). In an analysis of the relative influence of gender, type of treatment and age on anxiety levels, Stabholz & Peretz (6) showed that gender had the strongest influence on the overall dental anxiety, suggesting that dental anxiety may have a strong innate origin.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The finding that females reported higher dental anxiety is in accordance with many previous reports (2)(3)(4)(5)(6). In an analysis of the relative influence of gender, type of treatment and age on anxiety levels, Stabholz & Peretz (6) showed that gender had the strongest influence on the overall dental anxiety, suggesting that dental anxiety may have a strong innate origin.…”
Section: Discussionsupporting
confidence: 89%
“…Worldwide studies and studies conducted in Israel have determined that females tend to have higher anxiety levels than males (2)(3)(4)(5)(6). This trend has also been found among female medical students (7).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This was consistent with the results of other studies,[23242526] which found a considerably greater percentage of participants with DA. The mean DAS score of selected population (10.4 ± 4.13) was more than the score found by Peretz and Efrat[27] in Israeli population(9.49 ± 3.2) and Israeli kibbutz[28] population (8.98) and Pakistani (8.56 ± 3.59)[29] individuals. In relation to gender, we found that in the selected population, females scored higher on both fear measures, but the statistical analysis revealed no significant difference in this respect between the genders, which has been frequently noted in other studies[303132333435] of DA.…”
Section: Discussionmentioning
confidence: 60%
“…21 Dental students are constantly exposed to clinical procedures during their training (several of which they carry out themselves). 22 The exposure of these procedures becomes more when the students move from pre-clinical to clinical years. Therefore, it becomes commonsensical to anticipate that dental anxiety in students declines with the gradual progress in their education and clinical exposure.…”
Section: Discussionmentioning
confidence: 99%